Fixing another firm’s mistake: how should recovering firms react? - Bahmani, Navid; Jin, Zhenyu; Ghose, Sanjoy (The Journal of consumer marketing, 2020)
Purpose While within-firm service failure and recovery have been studied extensively, the context in which a service failure at one firm “spills over” and provides an opportunity for an external firm (a subsequent service provider) to recover (compensate) a customer has received limited attention. This study aims to examine how the extent of a service failure plays a role in how external firms should shape their recovery efforts, and how customers’ evaluations of the recovering firm and their feelings of unhappiness are affected. Design/methodology/approach A pretest conducted on MTurk gauged participants’ perceptions of equitability of the external firm’s recovery effort. In the main study, a 3 × 3 between-subjects experiment examined the effects of failure extent and external recovery type on evaluations of the recovering firm and reduced feelings of unhappiness. Findings It is found that equity judgments remain consistent in the external recovery context; transferred negative affect is able to be mitigate only in low-failure scenarios, and customers’ evaluations of the external firm increase only in high-failure scenarios. Research limitations/implications The use of hypothetical scenarios, as opposed to the employment of a field study, is the primary limitation of the study. Originality/value This research finds that external firms can reap the benefits of another firm’s service failure by offering no-cost recoveries, rather than ones that carry some form of cost.